Utilizing the combination of a digital microscope and Raman spectroscopy in determination the sequence of intersecting strokes from laser toner and water-based ink. (April 2019) - Sharaa, S.I.; El-Magd, A.A. Aboul; Bakr, A.A.; Moustafa, Y.M.; El-Aziz, I.M. Abd
Abstract: The authentication of the documents by experts mainly depends on determines the chronological order of strokes intersection. The samples consist of two types of intersections of a toner laser printer and water-based ink. Two nondestructive methods; digital microscope and Raman spectroscopy were used in the samples investigated. The effect of variations in the brands and models of laser printers, the influence of changes in brands of water-based ink, the nature of the paper surface and a time gap between the first and the second strokes on the determination of the sequence of intersecting strokes were studied. The four physical characteristics investigated under the digital microscope; the specular reflection, the ink glosses, gap and spreading determine the sequence of intersecting strokes except in case some colors of some pen brands. The results of Raman spectroscopy detect the sequence of intersecting strokes regardless of the colors or pen brands. The combination of a digital microscope and Raman spectroscopy can be considered as a scientific forensic base to determine the sequence of intersecting strokes of water-based ink and toner. Highlights: The samples investigated were consisting of two types of intersection resulting from toner and water-based ink pens. More than one factor perhaps effect on the determination of the sequence of intersecting strokes was studied. Two nondestructive methods; digital microscope and Raman spectroscopy were used in the samples investigated. Four physical characteristics are investigated under the digital microscope. The results of Raman spectroscopy detect the sequence of intersecting strokes regardless of the colors or pen brands.